A relational approach to improving interprofessional teamwork in post-partum haemorrhage (PPH) - Victoria Brazil; Darren McLean; Belinda Lowe; Lada Kordich; Deborah Cullen; Victoria De Araujo; Talia Eldridge; Eve Purdy (BMC, 2022)
Abstract Background Post-partum haemorrhage (PPH) is an obstetric emergency that requires effective teamwork under complex conditions. We explored healthcare team performance for women who suffered a PPH, focusing on relationships and culture as critical influences on teamwork behaviours and outcomes. Methods In collaboration with clinical teams, we implemented structural, process and relational interventions to improve teamwork in PPH cases. We were guided by the conceptual framework of Relational Coordination and used a mixed methods approach to data collection and analysis. We employed translational simulation as a central, but not singular, technique for enabling exploration and improvement. Key themes were identified from surveys, focus groups, simulation sessions, interviews, and personal communications over a 12-month period. Results Four overarching themes were identified: 1) Teamwork, clear roles and identified leadership are critical. 2) Relational factors powerfully underpin teamwork behaviours-shared goals, shared knowledge, and mutual respect. 3) Conflict and poor relationships can and should be actively explored and addressed to improve performance. 4) Simulation supports improved team performance through multifaceted mechanisms. One year after the project commenced, significant progress had been made in relationships and systems. Clinical outcomes have improved; despite unprecedented increase in labour ward activity, there has not been any increase in large PPHs. Conclusions Teamwork, relationships, and the context of care can be actively shaped in partnership with clinicians to support high performance in maternity care. We present our multifaceted approach as a guide for leaders and clinicians in maternity teams, and as an exemplar for others enacting quality improvement in healthcare.